2016
DOI: 10.1089/sur.2014.096
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Antibiotic Therapy for Severe Sepsis and Septic Shock

Abstract: Empiric antibiotic therapy was acceptable for severe sepsis and septic shock patients treated in the ICU. The appropriate selection of empiric antibiotics was related to a greater rate of de-escalation and better survival. The risk of multi-drug-resistant bacterial infections was not as high as expected, but will need further attention in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Meropenem, is an important option for the empirical treatment of cIAIs that exhibits a wide spectrum of activity against a variety of organisms, including polymicrobial, anaerobic bacteria and resistant flora that cause cIAIs. Moreover published treatment guidelines recommend meropenem as monotherapy or combination regimens for postoperative cIAIs (6), which is why we chose it as a comparator. However, empirical antibiotic therapy has been complicated by the growing emergence of drug-resistant organisms, particularly extended-spectrum β-lactamase-producing enterobacteriaceae, and by the overuse of carbapenemresistant bacteria, especially carbapenem-resistant klebsiella pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…Meropenem, is an important option for the empirical treatment of cIAIs that exhibits a wide spectrum of activity against a variety of organisms, including polymicrobial, anaerobic bacteria and resistant flora that cause cIAIs. Moreover published treatment guidelines recommend meropenem as monotherapy or combination regimens for postoperative cIAIs (6), which is why we chose it as a comparator. However, empirical antibiotic therapy has been complicated by the growing emergence of drug-resistant organisms, particularly extended-spectrum β-lactamase-producing enterobacteriaceae, and by the overuse of carbapenemresistant bacteria, especially carbapenem-resistant klebsiella pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current evidence available is not consistent. Several studies concluded that deescalation therapy was a protective factor associated with lower mortality in patients with severe sepsis, 4,5 while other studies have shown that de-escalation did not effect the mortality, 6,7 but increased the number of antibiotic days and the risk of superinfection. 6 Overall, there is a lack of adequate and firm evidence on whether de-escalation of empiric antibiotics therapy is effective for patients with severe sepsis and/or septic shock, due to the absence of sufficiently powered randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the undesired effects of de‐escalation interventions, one RCT ( n = 116) 104 showed that the 90‐day mortality rate was 78 more per 1,000 (95%CI: 64 fewer to 335 more). On the other hand, the mortality rate due to long‐term follow‐ups in 13 observational studies ( n = 3,635) 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 was 80 fewer per 1,000 (95%CI: 114 fewer to 40 fewer). The quality of the evidence for all of these was “very low.” The incidence of superinfections was 166 more per 1,000 (95%CI: 8 more to 539 more) in the RCTs; however, no observational studies have evaluated these outcomes.…”
Section: Methods Used For Creating This Guidelinementioning
confidence: 98%